P08.11 SURGICAL MANAGEMENT OF BRAIN METASTASES FROM LUNG ADENOCARCINOMA: A SINGLE CENTER EXPERIENCE AND REFLECTIONS ON MULTIPLE LESIONS - Fornaro, R. (Oxford University Press, 2014)
INTRODUCTION: Metastases are the most common intracerebral tumors, and they're expected to increase in the next years. Prognosis is linked to the progression of systemic and cerebral disease. Among patients in good conditions, removal of the cerebral metastasis represents the first treatment to apply. To evaluate the ideal conditions for surgery and its results we performed this single-center study on patients with solitary and multiple cerebral metastases. MATERIALS AND METHODS: We analyzed patients treated for cerebral metastasis between January 2004 and 2011. We considered only cases with non-small cell lung carcinoma (NSCLC) as primary tumor. We collected mortality and complication rates and analyzed the early outcomes before adjuvant therapy. Finally we used a χ2 test (p = 0.05) to assess if better early outcomes (improved or stable KPS) were significantly related to the presence of solitary VS multiple lesions. RESULTS: Our series included 199 patients; mean survival was 11.08 months. 95 patients harbored a single brain metastasis (Group 1) and 104 had more than one localization (Group 2). 67 patients underwent surgical operation. The mean pre-operative KPS was 75/100 in Group 1 and 65/100 in Group 2. After surgery in Group 1 the score improved in 69% of patients, was unchanged in 20% and worsened in 11%. In Group 2 the post-operative KPS was increased in 66% of cases, unchanged in 17% and worsened in 17% of cases. Statistical analysis did not show significant differences in the rates of good (KPS improved or stable) and poor outcomes in the two groups of operated patients. Patients with lesions in the posterior fossa improved after surgery more than those with supratentorial metastases. DISCUSSION: Observation of an high mortality for not-neurological causes confirms that modern treatments allow a significant control of the disease within the nervous system. Surgery entails the additional advantage of large tissue-samples availability for histological analysis that may influence targeted adjuvant therapies. The selection of surgical candidates should consider the patient conditions and size, number and location of the metastases. In the present cohort we observed a general improvement of quality of life related to surgery. 89% of patients in Group 1 and 83% in Group 2 underwent surgery without occurrence of additional impairment. Surgery was worth the risk to maintain a better quality of life. CONCLUSIONS: Management of cerebral metastases is a multidisciplinary job. Surgery allows an immediate control of local disease and can be considered also in multiple localizations. An accurate patient selection is related to acceptable quality of life in the months following surgery. Advances in the treatment of the systemic tumors is desirable for a significant improvement of the outcomes.